Programiranje industrijskih robotov - Karner, Timi; Gotlih, Janez (University of Maribor Press, 2022)
Industrial Robot Programming. The textbook covers the basics of programming, correct selection of industrial robots, layout, start-up, initial settings, tool coordinate system settings, workpieces, use of decision branches, repeating loops, interrupt routines, serial communication using PROFINET protocol and provides guidelines for safe return of robot to starting point. It also provides guidelines for preparing a robot for the operator.